PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPS SD NEGERI 81 PALEMBANG - Juarsyah; Erfan Ramadhani; Arief Kuswidyanarko (STKIP Subang, 2023)
This study aims to improve students' critical thinking skills in learning social studies in elementary school. The method used in this research is a quantitative method. The subjects in this study were 29 students of class V Elementary School. The data collection technique consisted of two stages, namely pretest and posttest. The results of the instrument item reliability test obtained pretest data of 0.757 and 0.758 posttest. From the results of the analysis of the data obtained through the fair sample T-test that the significance value is 0.20 > 0.05 so that Ho is rejected and Ha is accepted and it can be concluded that the discovery learning model has an increase in students' critical thinking skills.